Effects of different plyometric training frequencies on physical performance in youth male volleyball players: a randomized trial - Hernandez-Martinez, Jordan; Guzman-Muñoz, Eduardo; Ramirez-Campillo, Rodrigo; Herrera-Valenzuela, Tomas; Magnani Branco, Braulio Henrique; Avila-Valencia, Sergio; Luis Carter-Beltran, Juan; Aravena-Sagardia, Pablo; Méndez-Cornejo, Jorge; Valdés-Badilla, Pablo (Frontiers in Physiology, 2023)
This study aimed to analyze the effect of plyometric training (PT) at different frequencies on jump performance, running sprint speed, and service speed in youth male volleyball players. The participants were randomly assigned to one PT session per week (Experimental Group 1, EG1, n=15), two PT sessions per week (Experimental Group 2, EG2, n=14), and a control group (CG, n= 13). The total weekly jumping ranged between 98 to 196 jumps (equalized between EG1 and EG2). The assessments performed were squat jump (SJ), countermovement jump (CMJ), CMJ-arms, drop jump (DJ), 5-m sprint, 10-m sprint, and service speed. The intragroup comparisons showed that EG1 significantly (p< 0.001) improved SJ (Δ=12.74%; d=1.30), CMJ (Δ=11.94%; d=1.71), CMJ-arms (Δ=12.02%; d=1.47), DJ (Δ=10.93%; d=1.30), 5-m sprint (Δ=-4.61%; d=0.29), 10-m sprint (Δ=-3.95%; d=0.40) and service speed (Δ=8.17%; d=1.53). Similarly, EG2 significantly (p˂ 0.001) improved SJ (Δ=11.52%; d=1.25), CMJ (Δ=11.29%; d=1.38), CMJ-arms (Δ=11.42%; d=1.26), DJ (Δ=13.90%; d=2.17), 5-m sprint (Δ=-3.85%; d=0.25), 10-m sprint (Δ=-2.73%; d=0.25) and service speed (Δ=6.77%; d=1.44). The CG significantly (p< 0.05) improved SJ (Δ=2.68; d=0.28), CMJ-arms (Δ=2.30; d=0.35), 5-m sprint (Δ=-1.27; d=0.10) and service speed (Δ=1.42; d=0.30). Intergroup comparisons revealed significantly greater improvements in all variables (p< 0.001) in EG1 and EG2 concerning to CG. However, no significant differences were found between EG1 and EG2. A moderate weekly PT volume, distributed in one or two sessions per week, seems equally effective.